HARMONIZING FATWA AND POLICY: FURADA HAJJ IN SOUTHEAST ASIA THROUGH THE LENS OF MASLAHAH - Zainal Abidin; Ryas Maududdin; Muhammad Syahrul Sambu; Abriansyah; Muhammad Adryan (Academic Bright Collaboration, 2026)
This article examines how maslahah shapes fatwa and policy positions on Furada Hajj, a pilgrimage undertaken outside official quota systems, in Indonesia, Malaysia, Singapore, and Brunei. Using a qualitative-normative approach, it analyzes fatwas, pilgrimage regulations, policy documents, and fiqh literature through comparative fatwa analysis and usul al-fiqh, focusing on maslahah, maqasid al-shariah, sadd al-dzari‘ah, and ulil amri. The study finds that maslahah does not produce a uniform ruling. It operates as a flexible legal principle whose outcomes depend on institutional context, regulatory capacity, and definitions of public welfare. Indonesia and Malaysia support conditional permissibility because Furada Hajj may respond to long waiting periods and widen access, but only when consumer protection, ethical service standards, and state supervision are ensured. Singapore and Brunei apply maslahah more restrictively, prioritizing public order, administrative control, and protection from unregulated practices. Furada Hajj should not be treated as an unrestricted alternative to official quota systems. Its acceptability depends on transparent regulation, ethical management, consumer protection, and effective supervision. This study is limited to documentary and normative analysis without empirical interviews. The article shows how maslahah mediates between classical jurisprudence and modern pilgrimage governance in Southeast Asia by explaining why similar legal principles generate divergent yet contextually grounded policy outcomes across Muslim-minority and Muslim-majority settings in contemporary Hajj administration today.